The impact of Repeater on the Erlang Capacity of a CDMA Cellular System - Munee, Prapan; Keawboonsong, Pitak; Laowhasongkram, Phipat (Engineering and Applied Science Research, 2013)
This paper presents an evaluation of the Erlang capacity of a CDMA cellular system on the reverse link channel which employs repeater for all mobile within cell. The approximation methods will be based on Gaussian and Lognormal respectively, Numerical results show a decrease of the Erlang capacity as the number of repeaters increase. The Automatic On-Off Switching (AOS) repeater improvement increase the increase the Erlang capacity.